Monopoly capitalism in the digital era - Andrea Coveri; Claudio Cozza; Dario Guarascio (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2021)
The paper applies the radical view of Monopoly Capitalism to the digital platform economy. Based on the seminal ideas of Hymer and Zeitlin that led Cowling and Sugden to define the large monopolistic firm as a means to plan production from a unique centre of strategic decision-making, we attempt to develop a framework where digital platforms are conceived as an evolution of large transnational corporations. Power and control in our Monopoly Capitalism view are then meant not only in terms of market relations, but rather as levers for coordinating global production and influencing world societies. Applying this framework to the Amazon case, we highlight the key analytical dimensions to be considered: not only Amazon dominates other firms and suppliers through its diversification and a direct control of data and technology; its power is also linked to global labour fragmentation and uneven bargaining power vis-à-vis world governments, as in the Hymer and Cowling's tradition.
Keywords: L12; L22; P12; 330; Monopoly Capital; Monopoly Power; Digital Platforms; Amazon; Multinational corporation